Adult Periodic Alternating Nystagmus Masked by Involuntary Head Movements - Kaski, Diego; Haider, Salman; Male, Amanda; Radunovich, Alex; Liu, Fan; Cordivari, Carla; Bhatia, Kailash P.; Bronstein, Adolfo M. (Frontiers in Neurology, 2018)
Acquired periodic alternating nystagmus (PAN) describes a horizontal jerk nystagmus that reverses its direction with a predictable cycle, and is thought to arise from lesions involving the brainstem and cerebellum. We report a 20-year-old patient with PAN who presented with an acute vertiginous episode and developed an involuntary head movement that initially masked the PAN. The involuntary head movements were abolished with a subtherapeutic dose of botulinum toxin to the neck muscles. We propose that the head movements initially developed as a compensatory movement to the nystagmus, to maintain visual fixation in the presence of the underlying nystagmus, and became an entrained involuntary behavior. This case highlights the importance of disambiguating psychogenic from organic pathology as this may have clinical therapeutic implications, in this case resolution of the most disabling symptom which was her head oscillations, leading to improved day-to-day function despite PAN.